DETERMINANTS OF FINANCIAL STATEMENT FRAUD IN THE ENERGY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE 2020-2024 - Prayudha Pria Setya; Muhammad Firdaus; Jonathan Rafma Nanda S (International Journal Management and Economic, 2026)
Losses resulting from financial statement manipulation impact not only owners and internal management, but also investors, creditors, the government, and the public. This study analyzes industry characteristics, external pressures, justifications, and arrogant behavior by observing companies in the energy sector, including the oil, gas, and coal sub-sectors listed on the Indonesia Stock Exchange for 2020-2024. Sampling was conducted using a purposive sampling method on 16 companies out of 81 companies listed on the Indonesia Stock Exchange. The research data used were quantitative and secondary data. The analysis was conducted using a panel data regression method using Eviews software version 12. The results of the study indicate that there are indications of the influence of industry characteristics and justifications on fraud in manipulating financial statements, but there is no strong indication of the influence of external pressures and arrogant behavior on the occurrence of financial statement manipulation. There are loopholes in exploiting accounts receivable using fictitious sales, which impacts the recognition of profit/loss, as well as the justification of the company's accrual value which is engineered to achieve hidden goals. With a coefficient of determination of 20%, these factors were found to have a simultaneous influence on financial reporting fraud.